2010
DOI: 10.1111/j.1524-4725.2010.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Developing in Jadassohn's Sebaceous Nevus

Abstract: The authors have indicated no significant interest with commercial supporters. N evus sebaceous (or Jadassohn's sebaceous nevus or organoid nevus) is a well-known congenital skin hamartoma involving ectodermand mesoderm-derived structures that usually appears in the head and face area. During childhood, the lesion remains static but, during puberty, grows and becomes more evident and verrucous. These changes reveal growth of pilosebaceous and apocrine elements, probably because of the influence of androgens. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Benign tumors [12,27,28,29,30,31,32] are the most common neoplasms, including syringocystadenoma papilliferum, apocrine cystadenoma, trichoblastoma, trichilemmal cysts, and keratoacanthoma. Although less common, malignant degeneration [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47] occurs, with a lifetime risk of 5-20%. The majority of these tumors are basal cell carcinomas, but squamous cell, sebaceous, and apocrine carcinomas have also been recognized [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Benign tumors [12,27,28,29,30,31,32] are the most common neoplasms, including syringocystadenoma papilliferum, apocrine cystadenoma, trichoblastoma, trichilemmal cysts, and keratoacanthoma. Although less common, malignant degeneration [33,34,35,36,37,38,39,40,41,42,43,44,45,46,47] occurs, with a lifetime risk of 5-20%. The majority of these tumors are basal cell carcinomas, but squamous cell, sebaceous, and apocrine carcinomas have also been recognized [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Tumors observed together included BCC with SCC, sebaceous carcinoma, or KA and SCC with adnexal carcinoma. (3,8,9,10) Our case is very rare variant of SCC (acantholytic) that has not been reported to date arising in nevus sebaceous.…”
Section: Discussionmentioning
confidence: 69%
“…(6) Other types of benign neoplasms are trichilemmoma, sebaceoma, seborrheic keratosis, syringoma, poroma, nodular hidradenoma, apocrine cystadenoma, and nonepithelial proliferations such as melanocytic nevi. (7) The true incidence of malignant tumors occurring in lesions of NS is difficult to determine. In a review study done by Megan N, the most common malignancy observed was BCC.…”
Section: Discussionmentioning
confidence: 99%
“…Rodins K and Baillie L have reported a rare case of hybrid follicular cyst with matrical differentiation consisting of basaloid matrical-type cells with luminal shadow cell keratinization [12]. The malignant transformation potential of sebaceous nevi has been found to be less than 1% [13].…”
Section: Discussionmentioning
confidence: 99%
“…He suggested that these nevi are caused by effect of a few functionally abnormal clones. He categorized nevi in to two patterns, anatomical in which abnormal clone of cells are limited to the pathologic skin and functional, in which the two are spatially unrelated and hence may not follow Blaschko lines [12,13].…”
Section: Discussionmentioning
confidence: 99%